Interleukin 1 alpha inhibits prostaglandin E2 release to suppress pulsatile release of luteinizing hormone but not follicle-stimulating hormone. - Rettori, V (1991)
Interleukin 1 alpha (IL-1 alpha), a powerful endogenous pyrogen released from monocytes and macrophages by bacterial endotoxin, stimulates corticotropin, prolactin, and somatotropin release and inhibits thyrotropin release by hypothalamic action. We injected recombinant human IL-1 alpha into the third cerebral ventricle, to study its effect on the pulsatile release of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) in conscious, freely moving, ovariectomized rats. Intraventricular injection of 0.25 pmol of IL-1 alpha caused an almost immediate reduction of plasma LH concentration; this decrease was statistically significant 20 min after injection and occurred through a highly significant reduction in the number of LH pulses, with no effect on pulse amplitude. In contrast, there was no change in pulse frequency but a small significant elevation in amplitude of FSH pulses. Intraventricular injection of the diluent had no effect on gonadotropin release. The results provide further evidence for separate hypothalamic control mechanisms for FSH and LH release. To determine the mechanism of the suppression of LH release, mediobasal hypothalamic fragments were incubated in vitro with IL-1 alpha (10 pM) and the release of LH-releasing hormone (LHRH) and prostaglandin E2 into the medium was measured by RIA in the presence or absence of norepinephrine (50 microM). IL-1 alpha reduced basal LHRH release and blocked LHRH release induced by norepinephrine. It had no effect on the basal release of prostaglandin E2; however, it completely inhibited the release of PGE2 evoked by norepinephrine. To evaluate the possibility that IL-1 alpha might also interfere with the epoxygenase pathway of arachidonic acid metabolism, epoxyeicosatrienoic acids were also measured. IL-1 alpha had no effect on the content of epoxyeicosatrienoic acids in the hypothalamic fragments as measured by gas chromatography and mass spectrometry. In conclusion, IL-1 alpha suppresses LH but not FSH release by an almost complete cessation of pulsatile release of LH in the castrated rat. The mechanism of this effect appears to be by inhibition of prostaglandin E2-mediated release of LHRH.